2016
DOI: 10.1002/hep.28929
|View full text |Cite
|
Sign up to set email alerts
|

Functional defect of variants in the adenosine triphosphate–binding sites of ABCB4 and their rescue by the cystic fibrosis transmembrane conductance regulator potentiator, ivacaftor (VX‐770)

Abstract: ABCB4 (MDR3) is an adenosine triphosphate (ATP)‐binding cassette (ABC) transporter expressed at the canalicular membrane of hepatocytes, where it mediates phosphatidylcholine (PC) secretion. Variations in the ABCB4 gene are responsible for several biliary diseases, including progressive familial intrahepatic cholestasis type 3 (PFIC3), a rare disease that can be lethal in the absence of liver transplantation. In this study, we investigated the effect and potential rescue of ABCB4 missense variations that resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…Recently, the approved treatment with the CTFR potentiator ivacaftor (efficient in carriers of CF gating mutations) was found to be able to reverse the condition in human cells with ABCB4 class III mutations (►Table 1) that affect transporter activity as well. 82 These mutations (p.G535D, p.G536R, p. S1076C, p.S1176L, p.G1178S) are localized in conserved motifs involved in ATP binding and hydrolysis, and homologous to the gating mutations of CFTR. Novel therapeutic approaches for modulating bile composition in ABCB4 deficiency were investigated in Abcb4 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the approved treatment with the CTFR potentiator ivacaftor (efficient in carriers of CF gating mutations) was found to be able to reverse the condition in human cells with ABCB4 class III mutations (►Table 1) that affect transporter activity as well. 82 These mutations (p.G535D, p.G536R, p. S1076C, p.S1176L, p.G1178S) are localized in conserved motifs involved in ATP binding and hydrolysis, and homologous to the gating mutations of CFTR. Novel therapeutic approaches for modulating bile composition in ABCB4 deficiency were investigated in Abcb4 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Model of the 3D structure of the ABCB11 NBD1/NBD2 assembly was built with Modeller v9.15 13 using as a template the experimental structure of the MJ0796 NBD1/NBD2 heterodimer in complex with ATP (pdb 1l2t), 14 solved at 1.9 Å, as described previously for the modelling of the ABCB4 NBD1/NBD2 assembly. 12 We have used this MJ0796 3D structure, rather than other 3D structures sharing higher sequence similarities with ABCB11, because of the high resolution observed within the ATP-binding sites. The sequence alignment used for modelling is given in Figure S1.…”
Section: Lay Summarymentioning
confidence: 99%
“…10,11 Interestingly, it has been shown that ivacaftor could also increase the function of some MDR3 (multidrug resistance protein 3, ABCB4) mutants resulting from mutations located in NBDs and responsible for PFIC3, another chronic cholestatic liver disease. 12 However, the ability of potentiators to increase the function of BSEP mutants affecting BA transport activity has not been studied. BSEP ATP-binding sites having a strong similarity with those of CFTR and MDR3, we selected the p.T463I mutation, identified in a PFIC2 patient and located in the Walker-A motif of the first BSEP nucleotide binding domain (NBD1).…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Furthermore, ivacaftor did not overcome impaired PC secretion activity in a TMD mutant of ABCB4. 49 Residue L1580 is not directly located in the ATP binding site, however its mutation to a proline most likely breaks the helix, in which it is located. This will affect the upstream H-loop, which is also implicated in NBD dimerization and ATP binding.…”
Section: Discussionmentioning
confidence: 99%